Monoamine and Iron-related Toxicity : From Serotonin-binding Proteins to Lipid Peroxidation and Apoptosis in PC12 Cells (1998)
ABSTRACT: 1. Monoamines do not form coordination bonds with a preformed iron–serotonin-binding protein (SBP) complex, as initially believed. Instead, metals oxidize the monoamines either directly (manganese, copper) or by oxygen free radical formation (iron), the oxidation products bind covalently to SBP and the conjugates are able to undergo redox cycling. These interactions are denoted as a “molecular oxidative mechanism.” 2. Dopamine in combination with iron induces lipid peroxidation and apoptosis in PC12 cells by a stress oxidative-Ca2+ independent mechanism. 3. Dopamine–iron cytotoxicity may have relevance to an understanding of the mechanism by which dopaminergic neurons are eroded in some neurodegenerative disorders.